Potential therapeutic target genes for systemic lupus erythematosus: a bioinformatics analysis. Issue 1 (1st January 2021) - Yu, Yun; Liu, Liang; Hu, Long-Long; Yu, Ling-Ling; Li, Jun-Pei; Rao, Jing-an; Zhu, Ling-Juan; Liang, Qian; Zhang, Rong-Wei; Bao, Hui-Hui; Cheng, Xiao-Shu
ABSTRACT: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease involving multiple organs. However, the underlying etiology and mechanisms remain unclear. This study was performed to identify potential therapeutic targets for SLE using bioinformatics methods. First, 584 differentially expressed genes were identified based on the GSE61635 dataset. Tissue-specific analyses, enrichment analyses, and Protein–Protein interaction network were successively conducted. Furthermore, ELISA was performed to confirm the expression levels of key genes in the control and SLE blood samples. The findings revealed that tissue-specific expression of markers of the hematological system (25.5%, 28/110) varied significantly. CCL2, MMP9, and RSAD2 expression was markedly increased in the SLE samples compared with controls. In conclusion, the identified key genes ( CCL2, MMP9, and RSAD2 ) may act as possible therapeutic targets for the treatment of SLE. GRAPHICAL ABSTRACT: uf0001